The relationship between player skill level and golf shot "feel" estimation - Herder, P.; Benoit, L. (International Journal of Golf Science, 2022)
Motivation in the sports domain is one of the most commonly studied variables of the "athletic career." Using data from a recent survey of 69 elite mid-amateur male golfers from Canada and the United States, we drew on self-determination and achievement goal theories to understand whether these players were driven by intrinsic or extrinsic motives, or task or ego goal orientations. Informed by a lifespan approach, we also address how several life course factors, including childhood socioeconomic status, being a former collegiate athlete, marriage and family factors, and adulthood social class could be relevant predictors at the middle of the life course. Results suggest that the study participants were more likely to have task (intrinsic motivations) for playing elite mid-amateur golf. Former collegiate athletes were less likely to be motivated by extrinsic forces, while those raised in the upper class in childhood and those currently with a country club membership were much more likely to hold extrinsic, ego orientations. We discuss the implications of our findings for athletic motivation and participation in the mid-life context.